Impact of diabetes mellitus on short-term prognosis, length of stay, and costs in patients with acute kidney injury: A nationwide survey in China. - Lishan Tan; Li Chen; Yan Jia; Lingyan Li; Jinwei Wang; Xiaoyan Huang; Qiong Luo; Li Yang; Zuying Xiong; ISN AKF 0 by 25 China Consortium (PLoS ONE)
Background International data suggest that people with diabetes mellitus (DM) are at increased risk for worse acute kidney injury (AKI) outcomes; however, the data in China are limited. Therefore, this study aimed to describe the association of DM with short-term prognosis, length of stay, and expenditure in patients with AKI. Methods This study was based on the 2013 nationwide survey in China. According to the 2012 Kidney Disease: Improving Global Outcomes (KDIGO) and expanded criteria of AKI, 7604 patients with AKI were identified, and 1404 and 6200 patients were with and without DM, respectively. Clinical characteristics, outcomes, length of stay, and costs of these patients were compared. Multivariate regression analyses were conducted to evaluate the association of DM with mortality, failed renal recovery, length of stay, and costs. Results Patients with AKI and DM were older, had higher male preponderance (61.9%), presented with more comorbidities, and had higher serum creatinine levels compared with those without DM. An apparent increase in all-cause in-hospital mortality, length of stay, and costs was found in patients with DM. DM was not independently associated with failed renal recovery (adjusted OR (95%CI): 1.08 (0.94-1.25)) and in-hospital mortality (adjusted OR (95%): 1.16 (0.95-1.41)) in multivariate models. However, the diabetic status was positively associated with the length of stay (β = 0.06, p<0.05) and hospital expenditure (β = 0.10, p<0.01) in hospital after adjusting for possible confounders. Conclusion In hospitalized AKI patients, DM (vs. no DM) is independently associated with longer length of stay and greater costs, but is not associated with an increased risk for failed renal recovery and in-hospital mortality.